Design, fabrication and characterization of CMOS ISFET for pH measurements - Chin, Seng Fatt (Universiti Malaysia Perlis, 2011)
The Ion Sensitive Field Effect Transistor (ISFET) is a potentiometric pH sensor that is easily adapted to a wide range of chemical, biochemical and biomedical applications. The operation of an ISFET is based on the surface adsorption of charges from the test solution in the solid-electrolyte interface that is part of the gate of the ISFET. As a result of this process, the threshold voltage of the ISFET is modulated.This thesis describes the design, simulation, fabrication and characterization of ISFET for pH measurement of an aqueous solution. Prior to fabrication, the ISFET is simulated via TCAD TSUPREM4 process and MEDICI device simulator. The ISFET is fabricated in-house in the Micro Fabrication Cleanroom Laboratory (MFCL) at Universiti of Malaysia Perlis (UniMAP) by using CMOS fabrication technology. This goal is achieved due to the compatibility of ISFET and CMOS. Silicon nitride was used as an ion sensitive membrane and it was deposited by using Plasma Enhanced Chemical Vapour Deposition (PECVD) technique. A total of six masks were used in this fabrication to create the CMOS ISFET. The ISFET fabricated is aimed at pH measurement of aqueous solution. In order to obtain an accurate characterization of the ISFET, a semiconductor characterization system (SCS) comprises of a micro probe station and a parameter analyzer was utilized. For the analysis of ISFET in test solution, an Ag/AgCl electrode is used as a reference electrode and three types of standard aqueous pH buffer solutions of pH 4, pH 7 and pH 10 were used during the experiment of ISFET analysis. The sensitivity of the ISFETs measured is 40mV/pH for n-channel ISFET and 30mV/pH for p-channel ISFET. These results demonstrate that the in-house fabricated CMOS ISFET is functional as expected.